“Pretty Dope Way to Start a Story”: Fire Island (2022)’s Intertextual Dialogue with Jane Austen, Amy Heckerling, and Alice Munro - Ready, Kathryn (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2024)
Reviewers of the 2022 American film Fire Island, directed by Andrew Ahn and written by and starring Joel Kim Booster, have somewhat misleadingly characterized it as a straightforward transposition and modernization of Jane Austen’s Pride and Prejudice (1813). Such characterizations ignore the film’s marked intertextuality, including notable references not only to Amy Heckerling’s 1995 film Clueless, itself an adaptation of Austen’s Emma (1815), but also to Alice Munro’s 2004 short story collection Runaway. Fire Island reveals a complex dialogue with Austen, Heckerling, and Munro, as Booster confronts the declining state of reading culture in his socio-historical moment. Against Austen and Munro and with Heckerling, Booster concludes that the progressive intertwining of high and low culture in our modern moment is finally more to be celebrated than denigrated.